2010
DOI: 10.1210/me.2009-0487
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Receptor-Stimulated Progesterone Production by Preovulatory Granulosa Cells Requires Protein Kinase A-Dependent Activation/Dephosphorylation of the Actin Dynamizing Protein Cofilin

Abstract: Activation of the LH receptor (LHR) on preovulatory granulosa cells stimulates the cAMP/protein kinase A (PKA) pathway to regulate expression of genes required for ovulation and luteinization. LHR signaling also initiates rearrangement of the actin cytoskeleton. Because disruption of the actin cytoskeleton has been causally linked to steroidogenesis in various cell models, we sought to identify the cellular mechanisms that may modulate reorganization of the actin cytoskeleton and to determine whether cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 97 publications
2
37
0
Order By: Relevance
“…F-actin is reorganized from long fibers into a nondescript punctate distribution within both the cell body and extensions of granulosa cells (Karlsson et al, 2010). Consistent with our previous results (Karlsson et al, 2010), dual staining of cells with antibodies to vimentin and MAP2D showed that hCG promoted the contraction of granulosa cells and appearance of long cellular extensions (Fig. 1D).…”
Section: Map2d Colocalizes With the Vimentin Intermediate Filament Ansupporting
confidence: 89%
See 4 more Smart Citations
“…F-actin is reorganized from long fibers into a nondescript punctate distribution within both the cell body and extensions of granulosa cells (Karlsson et al, 2010). Consistent with our previous results (Karlsson et al, 2010), dual staining of cells with antibodies to vimentin and MAP2D showed that hCG promoted the contraction of granulosa cells and appearance of long cellular extensions (Fig. 1D).…”
Section: Map2d Colocalizes With the Vimentin Intermediate Filament Ansupporting
confidence: 89%
“…Untreated fixed granulosa cells appear flattened and fibroblastic with long bundles of phalloidin-stained F-actin (Karlsson et al, 2010). Staining with antibodies against β-tubulin, vimentin [the predominant intermediate protein in granulosa cells (Albertini and Kravit, 1981)], actin and MAP2D proteins also showed that each of these proteins reached into the periphery of the cells (Fig.…”
Section: Map2d Colocalizes With the Vimentin Intermediate Filament Anmentioning
confidence: 85%
See 3 more Smart Citations